Individual differences in extinction learning predict weight loss after treatment: A pilot study - van den Akker, Karolien (Eur Eat Disord Rev, 2020)
Learning theorists suggest extinction learning to be a central mechanism in weight loss success; however, empirical studies are scarce. In this pilot study, it was examined whether individual differences in extinction learning predict outcome after weight loss treatment. Overweight and obese individuals first completed a laboratory conditioning task in which individual differences in extinction learning were assessed. Next, they were randomised to one of two weight loss interventions: cue exposure therapy (CET), which is considered the clinical analogue of laboratory extinction, or a control lifestyle intervention. In line with expectations, better extinction learning in the laboratory task was associated with more weight loss at both post‐treatment (CET only) and follow‐up (both interventions) measurements. In contrast, two other indices of treatment success (reduction in overeating expectancies and ad libitum food intake during a laboratory taste test) showed no associations with pre‐treatment extinction learning. It is suggested that extinction learning may be a core mechanism underlying weight loss success, and hence, an important target for new obesity interventions.